Calculation of Structures Lying On an Anisotropic Basis - N, Dyussembayev I.; Z, Nigmetov M.; K, Suimenova M.; I, Izbassar A.; A, Dyussembayev (International Journal of Membrane Science and Technology, 2023)
The definition of the nucleus and the influence function of a transversally isotropic half-space is considered. Expressions of deflection and internal forces in an infinite base plate are obtained, taking into account their deepening into the rock mass, as well as the effect of the anisotropy of the base on the distribution of deflections and internal forces. The results obtained serve as a reference for the reconciliation of the results obtained by numerical and computer methods. This calculation algorithm allows us to estimate the bearing capacity of an anisotropic soil base.